2021
DOI: 10.3389/feart.2021.673753
|View full text |Cite
|
Sign up to set email alerts
|

Digital Rock Physics: A Geological Driven Workflow for the Segmentation of Anisotropic Ruhr Sandstone

Abstract: Over the last 3 decades, Digital Rock Physics (DRP) has become a complementary part of the characterization of reservoir rocks due to the non-destructive testing character of this technique. The use of high-resolution X-ray Computed Tomography (XRCT) has become widely accepted to create a digital twin of the material under investigation. Compared to other imaging techniques, XRCT technology allows a location-dependent resolution of the individual material particles in volume. However, there are still challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…We explored how the porosity changes with thresholding variations from the Otsu value. Otsu thresholding, in fact, proved to be among the best possible approaches to capture textural features of our rocks without further geological verifications (for details on geological driven workflows for rock segmentation please refer to Balcewicz et al 35 ). Our data shows that HR and VHR scans provide porosity values little affected by user/algorithm-selected parameters, while LR scan is very sensitive to threshold variations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We explored how the porosity changes with thresholding variations from the Otsu value. Otsu thresholding, in fact, proved to be among the best possible approaches to capture textural features of our rocks without further geological verifications (for details on geological driven workflows for rock segmentation please refer to Balcewicz et al 35 ). Our data shows that HR and VHR scans provide porosity values little affected by user/algorithm-selected parameters, while LR scan is very sensitive to threshold variations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang and Toksöz [203], Das et al [204], and Jänicke et al [205] used similar Digital Rock Physics (DRP) approaches to study attenuation mechanisms and fluid-solid interactions. Balcewicz et al [206] used DRP to study other properties. Focusing on enhancing an existing FO approach, Sun et al [116] tried to alleviate the experimental destructive subsonic resonances via numerical modelling to redefine their apparatus design.…”
Section: Shalesmentioning
confidence: 99%
“…It utilizes non-destructive methods to determine petrophysical properties. X-ray computed tomography (CT) or micro-computed tomography (micro-CT) are widely used to create three-dimensional (3D) rock volumes, serving as digital replicas of the materials under investigation [2][3][4][5][6]. These 3D volumes are typically employed for porosity computation through segmentation and for numerical simulations of permeability using the lattice Boltzmann method, which requires powerful and expensive high-performance computing clusters [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These 3D volumes are typically employed for porosity computation through segmentation and for numerical simulations of permeability using the lattice Boltzmann method, which requires powerful and expensive high-performance computing clusters [7][8][9]. In parallel, scanning electron microscopy (SEM) has demonstrated that not only 3D volumes but also 2D images can serve as supplementary aids to the 3D data [2,3,7,10]. SEM has also enabled the use of thin sections, which are prepared from rocks (plugs, cuttings) and do not possess a cylindrical shape, making them more suitable for CT and micro-CT analysis.…”
Section: Introductionmentioning
confidence: 99%